Population kinetics across the Indo-Pacific region : submitted in fulfillment of a Masters in Philosophy, Massey University, New Zealand - Aliev, Aydar (Massey University, 2014)
No abstract. The following is taken from the outline: The Pacific region provides a natural system to study complex admixture. From a broad perspective, there were two waves of settlement; the first 45,000 years ago (Melanesian), and the second, approximately 5,000 years ago (Asian) [1]. According to recent research, Asian ancestry does not decline gradually across Island Southeast Asia, but instead dramatically decreases, forming a cline [2]. There are several hypotheses explaining why there is a drastic, but not gradual, change in genetic ancestry proportions (Asian to Melanesian) across the region. One of these is a steep change in environmental conditions in Eastern Indonesia, which complicates rice cultivation [3]. Another explanation can be the switch from matri- to patriarchal social systems [4]. The main goal of this project is to explore demographic factors, such as migration and selection, to see if they can explain the genetic ancestry distribution. The main theoretical question that I will answer is: what is the reason behind the steep change in genetic ancestry proportion across eastern Indonesia? One of the reasons behind this could be cultural selection, although selection is just a hypothesis and the process might be selectively neutral. Anthropological data from the region are quite sparse, and this leads to the second goal of the project: to infer the history of modern Pacific populations using genetic data.
Keywords: Population, Indonesia; Population, Pacific region; Population, Indo-Pacific region; Population history, Indo-Pacific region; Genetic ancestry changes